HUBUNGAN INTERVENSI PERILAKU DALAM UKGS TERHADAP PENGETAHUAN ANAK USIA SD DI KOTA BATU - Tiara Putri Wahana (Jurnal Medika Hutama, 2024)
Teeth of elementary school age children are more susceptible to caries and trauma. There is a need for promotive and preventive program to protect children's teeth, one of which is UKGS. Behavioral interventions in the UKGS can be a source of information that can increase the dental and oral health knowledge of elementary school age children. The aim of the research was to determine the relationship between behavioral interventions in the UKGS program on the dental and oral health knowledge of elementary school age children in Batu City. The design method is quantitative research with analytical descriptive survey. This research used a cross sectional approach with multistage sampling. Obtained 116 samples by collecting data through questionnaires. Results showed that behavioral interventions in the UKGS program were carried out occasionally at SD Al-Fattah Integral, routinely at SDN Pandanrejo 2, and often at SDN Tlekung 2. The level of knowledge was good at 61.2%, moderate at 25%, and poor at 13.8%. Kendall's Tau correlation test obtained a correlation coefficient of 0.519 with a significance of 0.000. The conclusion is that there is a significant relationship between behavioral interventions in the UKGS program and dental and oral health knowledge in elementary school age children in Batu City with a strong correlation.